Through Maroon worlds: a conversation with Bonno Thoden van Velzen. Issue 2 (3rd May 2016) - Cunha, Olívia Maria Gomes da; Thoden van Velzen, H.U.E.
ABSTRACT: This article explores some of the writings of Dutch anthropologist H.U.E. (Bonno) Thoden van Velzen on the Ndyuka Maroon peoples of Suriname and Guyana, focusing particularly on the author's description of the role of gods, spirits, and other non-human beings in Maroon socialities and worlds. The first part of the article describes Thoden van Velzen's intellectual production, showing how his professional and political commitments to the Ndyuka led him to produce an ethnography on Ndyuka relationships with their ancestors, but also with the forests, rivers, sacred sites, and other beings with which Maroon people have negotiated their existence. In the second part of the article, the anthropologist himself speaks about his interactions with the Ndyuka in the Tapanahoni region in the 1960s, in an interview that addresses diverse levels of transformations in the knowledge on Maroon people.